Food safety makes me happy: using emotion to improve food safety training - Watkins, Tracee (Kansas State University, 2021)
Food safety education continues to be an important tool in the fight against foodborne illness. Using narratives in instruction can be more persuasive compared to traditional analytical delivery methods used in education and training. This research examined the effectiveness of both traditional educational videos, and videos using emotion evoking narrative techniques on food safety behavior outcomes. The extended transportation imagery model was employed as the theoretical basis for investigating the emotional and cognitive antecedents and outcomes of food safety interventions. The theory of planned behavior (TPB) was used as the framework for determining the relationship between emotional and cognitive outcomes of viewing food safety interventions, and measures of attitude, subjective norms, perceived behavioral control, and behavioral intention. The purpose of this research was to: (a) examine trainee (consumer) narrative involvement through their desire to experience emotion and likelihood to deeply interact with stories; (b) measure effectiveness of food safety videos and the level of emotional response they induce (c) compare emotional responses and training effectiveness of narrative, analytical, and combined interventions; and (d) determine how emotion impacts the TPB constructs. This study crowd sourced survey data from 502 participants. Mixed effect models and generalized estimating equations were used to explore the relationships between the antecedents and outcomes of narrative involvement for a group of 12 food safety videos, and then to investigate the relationship of emotional responses to TPB constructs after viewing narrative, analytical, and combined interventions about a single food safety topic. For the 12-video set, results indicated transportability and narrative characteristics were positive predictors of narrative involvement. Transportation positively predicted happiness and cognitive response. Narrative engagement positively predicted disgust, anxiety, fear, and sadness, and negatively predicted relaxation, and happiness. Training effectiveness was positively predicted by fear and happiness, while negatively predicted by disgust and sadness. For the analytical, narrative, and combined interventions, narrative involvement and cognitive response was higher for the narrative and combined interventions. Discrete emotion responses were lowest in the analytical intervention, and highest in the narrative. Perceived training effectiveness was highest for the combined intervention. Within the TPB framework, the analytical intervention was associated with lower levels of perceived behavioral control and the narrative was associated with higher levels of normative beliefs compared to the combined intervention. Four discrete emotions were found to effect TPB constructs. Anxiety positively predicted normative beliefs. Desire negatively predicted normative beliefs, attitude, and behavioral intention. Anger positively predicted normative beliefs, subjective norms, and perceived behavioral control. Disgust negatively predicted normative beliefs and perceived behavioral control. This study provides evidence for the use of discrete emotions, particularly anger and anxiety, in food safety training.
Keywords: Food safety; Theory of planned behavior; Emotion; Training